Structural and physical properties of collagen extracted from moon jellyfish under neutral pH conditions. Issue 10 (3rd October 2015) - Miki, Ayako; Inaba, Satomi; Baba, Takayuki; Kihira, Koji; Fukada, Harumi; Oda, Masayuki
Abstract: We extracted collagen from moon jellyfish under neutral pH conditions and analyzed its amino acid composition, secondary structure, and thermal stability. The content of hydroxyproline was 4.3%, which is lower than that of other collagens. Secondary structure analysis using circular dichroism (CD) showed a typical collagen helix. The thermal stability of this collagen at pH 3.0 was lower than those from fish scale and pig skin, which also correlates closely with jellyfish collagen having lower hydroxyproline content. Because the solubility of jellyfish collagen used in this study at neutral pH was quite high, it was possible to analyze its structural and physical properties under physiological conditions. Thermodynamic analysis using CD and differential scanning calorimetry showed that the thermal stability at pH 7.5 was higher than at pH 3.0, possibly due to electrostatic interactions. During the process of unfolding, fibrillation would occur only at neutral pH. Abstract: : CD and DSC analyses for the thermal denaturation of jellyfish collagen at pH 7.5 and 3.0 with its schematic